A large π-conjugated tetrakis (4-carboxyphenyl) porphyrin anode enables high specific capacity and superior cycling stability in lithium-ion batteries. Issue 76 (3rd September 2019) - Wu, Han; Zhang, Jianjun; Du, Xiaofan; Zhang, Min; Yang, Jinfeng; Zhang, Jinning; Luo, Ting; Liu, Hao; Xu, Hai; Cui, Guanglei
Abstract : Small HOMO–LUMO gaps that enable the facile uptake and release of electrons, which can improve the rate capability. Abstract : We demonstrated a novel single molecule – tetrakis(4-carboxyphenyl) porphyrin (TCPP) with a large π-conjugated system as a high-performance organic anode of lithium batteries. It was found that this TCPP displayed relatively low solubility (<0.1 mg mL −1 ) in a 1 M LiDFOB/PC electrolyte, high reversible specific capacity ( ca. 1200 mA h g −1 at 358 mA g −1 ), excellent rate capability (548.4 mA h g −1 at 8 A g −1 ) and superior cycling performance (capacity retention of 89% after 2500 cycles at 6 A g −1 ).